2005
DOI: 10.1037/0735-7044.119.3.752
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular Self-Administration of Commonly Abused Anabolic-Androgenic Steroids in Male Hamsters (Mesocricetus auratus): Nandrolone, Drostanolone, Oxymetholone, and Stanozolol.

Abstract: Previous studies by the authors have shown voluntary intracerebroventricular (icv) testosterone self-administration in hamsters (Mesocricetus auratus). Here, the authors compared icv self-administration of 4 anabolic steroids (drostanolone, nandrolone, oxymetholone, and stanozolol) at 0.1, 1.0, and 2.0 microg/microl, each for 8 days. Males (n=8/group) showed the highest levels of operant behavior for injectable steroids (drostanolone, nandrolone) compared with orally active androgens (oxymetholone, stanozolol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
2
11
1
1
Order By: Relevance
“…Animal research has shown that rodents exhibit conditioned place preference for locations associated with testosterone administration (Alexander et al, 1994;Arnedo et al, 2000Arnedo et al, , 2002de Beun et al, 1992;Frye et al, 2002) and self-administer testosterone both orally (Johnson and Wood, 2001) and intracerebroventricularly (Ballard and Wood, 2005;Wood, 2004, 2006b;Peters and Wood, 2005;Triemstra and Wood, 2004;Wood et al, 2004). Similar effects were observed when testosterone (Packard et al, 1997) or its metabolites (Frye et al, 2002) were infused directly into the nucleus accumbens (NAcc), and these effects were shown to be blocked by dopamine (DA) receptor antagonists (Packard et al, 1998;Schroeder and Packard, 2000).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Animal research has shown that rodents exhibit conditioned place preference for locations associated with testosterone administration (Alexander et al, 1994;Arnedo et al, 2000Arnedo et al, , 2002de Beun et al, 1992;Frye et al, 2002) and self-administer testosterone both orally (Johnson and Wood, 2001) and intracerebroventricularly (Ballard and Wood, 2005;Wood, 2004, 2006b;Peters and Wood, 2005;Triemstra and Wood, 2004;Wood et al, 2004). Similar effects were observed when testosterone (Packard et al, 1997) or its metabolites (Frye et al, 2002) were infused directly into the nucleus accumbens (NAcc), and these effects were shown to be blocked by dopamine (DA) receptor antagonists (Packard et al, 1998;Schroeder and Packard, 2000).…”
Section: Introductionmentioning
confidence: 59%
“…AAS are tailored to maximize anabolic effects but clearly still have androgenic and reinforcing potency (Ballard and Wood, 2005). Studies of prolonged AAS use in athletes have revealed classic signs of dependence, with hypomanic symptoms during use and depression related to withdrawal, although findings were not always consistent and not all studies are well controlled (Wood, 2008).…”
Section: Contrast/regionmentioning
confidence: 98%
“…These “hedonic” effects may vary across different AAS (Ballard and Wood, 2005), and may be modulated by synergistic effects of other drugs such as alcohol (Johansson et al, 2000; Lindqvist et al, 2002) and stimulants (Kurling et al, 2008). A hedonic mechanism of AAS dependence is supported by observations of the reinforcing effects of androgens in laboratory animals—since animals are presumably not motivated by body-image concerns or anticipation of hypogonadism.…”
Section: The Hedonic Mechanismmentioning
confidence: 99%
“…Alguns estudos 10,11 também investigaram mecanismos moleculares cerebrais relacionados aos efeitos comportamentais de altas doses de 23 afirmam que existem três tipos principais de modificações da molécula de testosterona tais como: a hidroxilação na posição C-10 para aumentar a potência relativa (p.ex., nandrolona); esterificação para diminuir a taxa de inserção em circulação (por exemplo, cipionato de testosterona 24 ; e alquilação na posição C-17 para reduzir a primeira passagem do metabolismo no fígado, permitindo assim a administração oral, por exemplo, estanozolol [25][26][27] . Através disso podemos inferir que a ação do Winstrol ® foi maior que a do Deposteron ® devido ao processamento pelo qual o Winstrol ® (Stanozolol) passou (alquilação na posição C-17), que permitiu a utilização desse por via oral.…”
Section: Discussionunclassified